KENDALA YANG DIHADAPI DALAM PELAKSANAAN PROGRAM PEMBINAAN WARGA BINAAN PADA LAPAS KELAS IIB TANJUNG PATI PAYAKUMBUH - Ramadhina, Annisa Qinaya (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2025)
This research explores the challenges encountered in implementing inmate development programs at Class IIB Correctional Facility in Tanjung Pati, Payakumbuh. The study aims to identify and analyze the key constraints that hinder the effectiveness of correctional programs designed to rehabilitate inmates through personality and vocational development. Utilizing a qualitative descriptive method, data were collected through interviews, observations, and documentation involving correctional officers and inmates as primary sources. Findings indicate that the primary challenges include limited human resources, inadequate infrastructure, lack of access to educational materials, minimal stakeholder involvement, and market constraints for products created through vocational training. These obstacles significantly affect the consistency and quality of rehabilitation efforts, leading to a gap between program design and actual implementation. The study highlights the need for strategic improvements in resource allocation, program supervision, and community partnership to optimize the role of correctional institutions in preparing inmates for reintegration into society.